ANALISIS MINAT BELAJAR SISWA PADA SAAT PEMBELAJARAN PJOK DI SLB LAVENDER BANGKALAN - Asyari, Sayr Dzikrullah Al; Purwoto , Septyaningrum Putri; Handayani, Heni Yuli (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Adaptive physical education involves modifying physical education to address the needs of students with disabilities. This study aims to assess the level of interest in learning among students with special needs (ABK) during PJOK classes at SLB Samudra Lavender Bangkalan. The research employs a quantitative descriptive approach using a survey method. Data was gathered through a questionnaire administered to 28 students at SLB Samudra Lavender Bangkalan. The findings reveal that the average level of student interest in PJOK was 60.98%. Among the 28 students, only 1 exhibited a medium level of interest in PJOK, representing 3.57%, while 27 students, or 96.43%, showed a low level of interest. The study concludes that the level of interest in PJOK at SLB Lavender is categorized as low. Therefore, it is recommended that improvements in teaching methods be implemented to enhance students' interest in PJOK.